STAFF NEWS. (Historic New Orleans Collection Quarterly)
The article announces career developments involving The Historic New Orleans Collection staff, including the appointment of Justin Sweatt as computer client services technician, the retirement of manager Steve Sweet, and Molly Reid Cleaver's completion of a master's program at Tulane University.